Therapeutic effects and mechanisms of Xinmaitong formula for type 2 diabetes mellitus via GLP-1R signaling - Pu, Weidong; Pan, Yang; Yang, Kang; Gao, Jian; Tian, Fen; Song, Jingrui; Huang, Yubing; Li, Yanmei (Frontiers in Pharmacology, 2025)
IntroductionTraditional Chinese Medicine (TCM) theory posits that type 2 diabetes mellitus (T2DM) characterized by Qi and Yin deficiency, is associated with elevated blood lipid levels. The Xinmaitong formula (XMT) is a folk remedy believed to lower blood lipid levels. However, the functional components and molecular mechanisms through which XMT exerts its anti-diabetic effects remain to be elucidated. This study aimed to investigate the therapeutic effects and potential mechanisms of XMT in the treatment of T2DM, focusing on the glucagon-like peptide-1 receptor (GLP-1R) signaling pathway.MethodsA TCM formula that promotes GLP-1R expression was screened using a GLP-1R promoter-dependent luciferase reporter gene vector (PGL3-GLP-1R-luc). The T2DM mouse model was established using a high-fat diet and streptozotocin (STZ). Blood glucose levels were measured using a glucometer and oral glucose tolerance test (OGTT). Serum biochemical parameters and insulin levels were also assessed. Organ pathology in mice was evaluated using hematoxylin and eosin (H&E) staining. Immunofluorescence (IF) was employed to observe changes in insulin and GLP-1R expression in the pancreas of mice. The effects of medicated serum on Min6 cell growth were examined using a methyl thiazolyl tetrazolium (MTT) assay. A Min6 cell injury model was established to detect cAMP and Ca2+ concentrations. Ultra high-performance liquid chromatography-mass spectrometry (UHPLC-MS) was used to identify blood-absorbed components of XMT.ResultsLuciferase reporter constructs driven by GLP-1R promoter response elements analysis identified that TCM formula XMT promoted GLP-1R expression. In vivo experiments demonstrated that XMT significantly reduced fasting blood glucose levels in T2DM mice and improved OGTT results. It also exhibited protective effects on islet tissues, notably increasing GLP-1R expression and insulin secretion in the pancreas. Biochemical markers indicated no significant adverse effects on liver or kidney function following XMT administration. After treatment with palmitic acid (PA), GLP-1R expression in Min6 cells was significantly decreased. However, treatment with XMT upregulated GLP-1R expression. Additionally, cyclic adenosine monophosphate (cAMP) and Ca2+ exhibited substantial improvements, and the key pancreatic growth protein PDX1 was activated.ConclusionXMT exerts hypoglycemic effects by upregulating GLP-1R gene expression, enhancing GLP-1R protein synthesis, and subsequently promoting cAMP release. This process activates Ca2+ influx in pancreatic β-cells, triggering insulin exocytosis from islet cells.